Структурирование учебника на основе интерактивной модульной технологии обучения - Артыкова, Т.М. (My University, 2016)
It is very productive to look through this point as a system of functions in the sphere of fundamentals of the textbook. The author of this article made an effort to analyze on her experience and to prove the means of realization one of the leading functions- systematization and showed the construction of the material on the basis of pedagogical technology. The workout of the conception of the new generation of textbooks became actual, that’s why the author considered to ground the necessity of realization of new requirements.
Keywords: system; pedagogical technology; systematization; textbooks